2007
DOI: 10.1016/j.ejheart.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for seeking acute care in chronic heart failure

Abstract: Background: Patients with chronic heart failure (CHF) have frequent episodes of exacerbation leading to recurrent hospitalization. Aims: To explore factors related to patients seeking care for worsening CHF. Methods: Eighty-eight patients diagnosed with a deteriorating CHF condition were interviewed. Data were analysed using content analysis. Results: Overall, 51 (58%) patients sought emergency care because of their symptoms while 37 (42%) were either sent by relatives or referred from outpatient clinics. Dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(219 citation statements)
references
References 29 publications
9
207
2
1
Order By: Relevance
“…Recent studies reveal that patients with CHF reported, on average, between three and eight symptoms (Nordgren & Sörensen, 2003;Patel, et al, 2006). The most prevalent symptoms reported by the patients were, in addition to dyspnea and fatigue, dry mouth, diffi cult sleeping, bodily pain and loss of balance.…”
Section: Symptoms In Patients With Chronic Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reveal that patients with CHF reported, on average, between three and eight symptoms (Nordgren & Sörensen, 2003;Patel, et al, 2006). The most prevalent symptoms reported by the patients were, in addition to dyspnea and fatigue, dry mouth, diffi cult sleeping, bodily pain and loss of balance.…”
Section: Symptoms In Patients With Chronic Heart Failurementioning
confidence: 99%
“…The most prevalent symptoms reported by the patients were, in addition to dyspnea and fatigue, dry mouth, diffi cult sleeping, bodily pain and loss of balance. Commonly reported psychological symptoms were diffi culty concentrating, anxiety and depressed mood (Bennett et al, 2000;Zambroski et al, 2005;Patel et al, 2006). Patients with end-stage heart failure had symptoms similar to those of cancer and frequently reported nausea, loss of appetite and constipation (Nordgren & Sörensen, 2003).…”
Section: Symptoms In Patients With Chronic Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3 Patients often need complex care due to old age, cognitive decline, co-morbidities and polypharmacy. 4 The health care resources for these patients have been reported as not meeting the patients' needs.…”
Section: Introductionmentioning
confidence: 99%
“…{{4739 Goff The only other study examining emotional factors and delay was qualitative. The study by Patel et al (2007) reported that among patients with a diagnosis of deteriorating HF, 11% seeking medical care because they felt that their situation was hopeless. For instance, they perceived that seeking treatment was useless because there is no cure for HF.…”
Section: Patient Responses: Self-care Mode Of Transportation For Carmentioning
confidence: 99%